Is Airport Experience a Critical Antecedent for Destination Revisit? The Role of Environment in the Covid-19 Era - Yerimou, Pantelitsa; Panigyrakis, George G.; Themistocleous, Christos (My University, 2022)
Despite the significance of airport atmospherics and visitors’ experiences, relatively few studies address the effect of both the airport environment and experience on the intentions to revisit the destination. This study draws new insights by examining (1) the influence of airport atmospherics on airport experience and willingness to revisit a destination, and (2) the effect of the overall experience evaluations on the intentions to revisit the host country. Sense of place’s moderating role on the relationship between atmospherics, experience and destination revisit is also examined. A mixed-method approach was employed; an exploratory qualitative focus group study with industry professionals, and a survey comprised of 604 international travellers. The proposed framework was tested through Structural Equation Modelling. In light of the study’s findings, it was revealed that airport atmospherics serve as strong indicators of overall experience evaluations as well as of the willingness to revisit the destination. Additionally, evidence indicate that sense of place did not have a moderating effect in the aforementioned relationships, with respective managerial implications concerning the use of atmospheric stimuli in the airport context and recommendations for future research being provided.
Keywords: Consumer Behaviour; Airport atmospherics; Destination revisit